IMPLEMENTASI PEMBELAJARAN FIQIH BERBASIS LIFE SKILL DI MI AL HASAN KEC. SUMPIUH KABUPATEN BANYUMAS - Siswadi siswadi (Jurnal Penelitian Agama, 2016)
Abstract: Fight's learning materials in MI Al Hasan Sumpiuh subdistrict, Banyumas already provides an understanding, not just lecture and question and answer but has integrated with the practice of the material itself. The results of this study are, first, the implementation of jurisprudence learning in MI Al Hasan leads to life skills to maximize the learning component that is (a) teaching materials (b) learning model (c) learning methods, and (d) a medium of learning. Second, supporting factors include the control of the madrasas, mastery of materials by teachers, madrasah's support activities. Inhibiting factors include the unpreparedness of teachers in teaching, students' abilities are different, the lack of time lesson. Keywords: Madrasah, Fight, Life skill.